U.S. Poverty and Income Security Policy in a Cross National Perspective: The War On Poverty - What Worked? - Timothy Smeeding (Luxembourg Income Study (LIS), 1991)
The effectiveness of tax and transfer systems in removing low income families of all ages from poverty is compared across eight nations. The paper shows the relative ineffectiveness of the U.S. tax and transfer system in meeting the needs of its poor children, elderly and adults compared to other nations.
Keywords: 330